Efficient Conversion of Agroindustrial Waste into D(-) Lactic Acid by Lactobacillus delbrueckii Using Fed-Batch Fermentation - Beitel, Susan Michelz [UNESP]; Coelho, Luciana Fontes [UNESP]; Contiero, Jonas [UNESP] (Wiley, 2020)
Purpose. The goal of this paper is to describe the green conversion of agricultural waste products, such as molasses and corn steep liquor, into large amounts of D(-) lactic acid using a facilitated multipulse fed-batch strategy and affordable pH neutralizer. This is a very low-cost process because there is no need for hydrolysis of the waste products. The fed-batch strategy increases lactic acid productivity by avoiding inhibition caused by a high initial substrate concentration, and the selected controlling agent prevents cell stress that could be caused by high osmotic pressure of the culture media. Methods. The effects of different carbon and nitrogen sources on lactic acid production were investigated, and the best concentrations of the medium components were determined. To optimize the culture conditions of the Lactobacillus delbrueckii strain, the effects of pH control, temperature, neutralizing agent, agitation, and inoculum size in batch cultures were investigated. Fed-batch strategies were also studied to improve production and productivity. Result. A high titer of D(-) lactic acid (162g/liter) was achieved after 48 hours of fermentation. Productivity at this point was 3.37 g/L·h. The optimum conditions were a temperature of 39°C, pH 5.5 controlled by the addition of Ca(OH)2, agitation at 150 rpm, and inoculum size of 25% (v/v). Conclusion. The production of high optical purity D(-) lactic acid through L. delbrueckii fermentation with molasses and corn steep liquor is a promising economical alternative process that can be performed on the industrial scale.